Cultural Anatomies of the Heart in Aristotle, Augustine, Aquinas, Calvin, and Harvey - Boyle, Marjorie O'Rourke (Springer International Publishing, 2018)
This book probes beneath modern scientific and sentimental concepts of the heart to discover its past mysteries. Historical hearts evidenced essential aspects of human existence that still endure in modern thought and experience of political community, psychological mentality, and physical vitality. Marjorie O'Rourke Boyle revises ordinary assumptions about the heart with original interdisciplinary research on religious beliefs and theological and philosophical ideas. Her book uncovers the thought of Aristotle, William Harvey, Augustine, Thomas Aquinas, and John Calvin as it relates to the heart. It analyzes Augustine's outlaw heart in cultural deviance from biblical law; Aquinas's problematic argument for the permanence of the natural law in the heart; and Calvin's advocacy for an affective heart re-created by the Spirit from its fallen nature. This book of cultural anatomies is the climax of her dozen years of publications on the heart.